Covalent layer-by-layer thin films with charge-transfer chromophores: side chain engineering for efficient Ag+ ion recognition in aqueous solutions. Issue 44 (5th November 2018) - Fujita, Hiroyuki; Michinobu, Tsuyoshi
Abstract : Covalent layer-by-layer films, fabricated by [2+2] cycloaddition–retroelectrocyclization, show different Ag + ion recognition behaviors due to the side-chain groups of precursor polymers. Abstract : Covalent layer-by-layer (LbL) thin films are fabricated by a highly efficient [2+2] cycloaddition–retroelectrocyclization (CA–RE) reaction of aniline-substituted alkyne and 7, 7, 8, 8-tetracyanoquinodimethane (TCNQ) moieties. Polystyrene bearing aniline-substituted alkyne side chains and TCNQ polyester were prepared as precursor polymers, then sequentially deposited and fixed by covalent bonds on an indium-tin-oxide (ITO) substrate. The successful alternate growth of the films was demonstrated by many techniques including absorption spectroscopy, surface roughness, and redox activities. Interestingly, the water contact angles of the film surface were dependent on the side chains of the polystyrene derivatives. When hydrophilic triethylene glycol was employed, the surface hydrophilicity was similar to that of the TCNQ polyester. In contrast, the use of hydrophobic n -hexyl groups resulted in a significant difference in the water contact angles between the polystyrene and TCNQ polyester. A similar difference occurred when the Ag + ion recognition was studied by soaking the LbL films in aqueous solutions. The LbL films constructed from the polystyrene with triethylene glycol chains displayed a more rapid and significant recognition of Ag + ions than those constructed from the polystyrene with n -hexyl chains.